2014
DOI: 10.3389/fmicb.2014.00682
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal-induced calmodulin mediated changes in antioxidant enzymes and growth response of drought-stressed trifoliate orange

Abstract: Trifoliate orange [Poncirus trifoliata (L) Raf.] is considered highly arbuscular mycorrhizal (AM) dependent for growth responses through a series of signal transductions in form of various physiological responses. The proposed study was carried out to evaluate the effect of an AM fungus (Funneliformis mosseae) on growth, antioxidant enzyme (catalase, CAT; superoxide dismutase, SOD) activities, leaf relative water content (RWC), calmodulin (CaM), superoxide anion (O2•−), and hydrogen peroxide (H2O2) concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 41 publications
(49 reference statements)
11
28
1
Order By: Relevance
“…It seems that AMF inoculation was involved in the increase in root soluble protein concentrations under DS. Similar finding was reported by Huang et al (2014) in trifoliate orange plants. The increase of soluble protein under mycorrhization might be involved in the decrease in RNA disintegration and in stimulating new protein production under DS.…”
Section: Changes In Root Soluble Proteinsupporting
confidence: 79%
“…It seems that AMF inoculation was involved in the increase in root soluble protein concentrations under DS. Similar finding was reported by Huang et al (2014) in trifoliate orange plants. The increase of soluble protein under mycorrhization might be involved in the decrease in RNA disintegration and in stimulating new protein production under DS.…”
Section: Changes In Root Soluble Proteinsupporting
confidence: 79%
“…Likewise 28.65%, 35.15%, 27.94% and 15.01% significantly higher leaf CaM concentration was observed in C. etunicatum, D. versiformis, F. mosseae, and R. intraradices, respectively, over non-AMF-seedlings. These results are in agreement with the results of Huang et al (2014) in trifoliate orange. Strong correlation of NO and CaM with root AMF colonization suggested that, root AMF colonization could be driven through NO and CaM (Huang et al, 2014).…”
Section: Response On Leaf No and Camsupporting
confidence: 83%
“…These results are in agreement with the results of Huang et al (2014) in trifoliate orange. Strong correlation of NO and CaM with root AMF colonization suggested that, root AMF colonization could be driven through NO and CaM (Huang et al, 2014). Leaf NO and CaM also correlated positively with root total length and number of LR in first order, indicating that AMF-induced NO and CaM as a signalling molecule are partly involved in the root development.…”
Section: Response On Leaf No and Camsupporting
confidence: 83%
“…Chabaud et al (2011) indicated that exudates from AMF spores induced Ca 2+ rapid increase and Gleason et al (2006) further proved that Ca 2+ /CaM regulated calcium and calmodulin-dependent kinase (CCaMK) and induced specific gene transcription. Huang et al (2014) reported that inoculation with F. mosseae increased CaM level and promoted the resistance to drought stress in trifoliate orange. In this work, inoculation with AMF activated root CaM level in donor seedlings, and subsequent CMN colonization also promoted root CaM increase in receptor seedlings.…”
Section: Discussionmentioning
confidence: 99%